CORRELATION BETWEEN PROGESTERONE HORMONE CONCENTRATION AND NUMBER OF FETUSES OF ETAWA CROSSBRED GOAT IN DIFFERENT GESTATION PERIOD - Syafruddin Syafruddin; Khairul Rizal; Rosmaidar Rosmaidar; Juli Melia; roslizawaty roslizawaty; Zuhrawati Zuhrawati; Erdiansyah Rahmi; Mahdi Abrar (Universitas Syiah Kuala, 2017)
This study aimed to investigate the correlation between progesterone hormone concentration and number of fetus as well as the difference in progesterone hormone concentration from different gestation periods in Etawah crossbred (EC). Five EC goats used in this study were injected with 2 mL of 5.5 mg prostaglandin F2α (PGF2α, Capriglandin) intramuscularly, with an interval of 10 days. Goats that showed symptoms of estrus were mated naturally with male goats. Blood samples were taken on the 7th, 14th, 21st, and 75th days of gestation. Progesterone hormone concentration was determined using enzyme linked immunosorbent assay (ELISA). The number of fetus was determined at 35th gestational day using ultrasonography (USG). Four out of 5 goats were found to have 1 fetus and 1 goat had 2 fetuses. The progesterone concentration on the 7th, 14th, 21st, and 75th days of gestation in goats with single fetus were 5.21, 7.78, 11.97, and 18.78 ng/mL, respectively, while in goat with two fetuses were 8.44, 14.53, 16.81, and 22.73 ng/mL, respectively. The correlation (r) between progesterone hormone concentration and number of fetus on the 7th, 14th, 21st, and 75th days of gestation were 0.442, 0.854, 0.592, and 0.757, respectively. It is concluded that progesterone concentrations are highly correlated to the number of fetus in each gestation period in EC goats.